Pengembangan Aplikasi E-Recruitment Berbasis Website Studi Kasus PT. Mitra Moderen Marketama - Rafi Rizq Ramadhan; Harya Bima Dirgantara (UNIVERSITAS KALBIS, 2026)
The goal of this research is to develop a web-based recruitment application to address challenges in the employee recruitment process, which involves a large number of applicants and limited time. This application is designed to simplify and expedite the entire recruitment process through the use of a web-based platform. The method applied in the development of this application is the Rational Unified Process (RUP). The application is tested using black box testing and user acceptance test methods. The results of this research include a web-based recruitment system developed using the Rational Unified Process method.